PENGEMBANGAN PERMAINAN KARTU KWARTET SEBAGAI MEDIA PEMBELAJARAN BIOLOGI KELAS XI IPA SMAN 4 LUWU TIMUR - Anjar Tri Saputra; Ilyas Ismail; Zulkarnaim Umar (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2019)
This study aims to develop a quartet card game as a biology learning media in the excretion system subject that meets the feasibility value of validity, practicality, and effectiveness. The process of developing the media uses the 4D development model, namely defining, designing, developing, and disseminating. The research subjects were students of class XI IPA 3of East Luwu, 4 High School. The research instruments used were validation sheets, teacher workforce activity and observation sheets for students' activities as well as teacher response questionnaires, student response questionnaires and test items. Based on data analysis showed the validity level of quartet card game learning media is in valid category with an average value of 3.18 (x> 2.5). The results of data analysis obtained for the practicality assessment of the educator's activity sheet and the student's observation sheet and teacher's response, the practical level of the learning media are in the very high category with an average total score of 3.85 (x> 3.4). The results of data analysis obtained from student learning tests, quartet card game learning media is categorized as effective because 80.77% of students achieve classical completeness of learning and responses of students in the very positive category with a percentage of 100%. The results of this development are worth considering as one of media that can be used in the learning process in the classroom.Kata kunci:4 –D development model, quartet card game , excretion system